Literary publishing in the Baccalaureate: Marginalised voices of the 19th century. A didactic proposal for 1st Baccaluareate (Ogigia. Revista Electrónica de Estudios Hispánicos, 2022)
Literary education is a fundamental pillar in shaping students' critical thinking through shared cultural references. However, there is an unbalanced presence of female and male references that goes against coeducation. Both the school canon and literary publishing continue to perpetuate sexist patterns that relegate women of letters to second place in history. For this reason, it is necessary to reconfigure both and to revise the contents that are brought to the classroom to make women visible, in order to transmit values of equality and respect to students. The aim of this work is to create a proposal for innovation, aimed at educational improvement, in which students reflect on the role that literary publishing plays both in their education and in their formation as individuals.
Keywords: literary education; women writers; school canon; literary publishing; coeducation